Implementation of Encryption Techniques on Computer Networks For Data Security In Review of reliability - Maria Maria Ulfa (Majalah SIKOMTEK, 2005)
Issues of security and confidentiality of data is one important aspect of information systems.In this case, is closely related to how important such information and data sent and receivedby a person of interest. Information will be no longer useful in the middle of the road whenthe information was intercepted (dihecker) by people who are not responsible or eligible. Inthis paper we discuss about the security of data in a computer network system usingencryption techniques (encryption) PGP (Pretty Good Privacy) are reviewed in terms ofreliability. PGP is used to encode a file so that only the intended person or the owner re-filesthat can describe and create digital signatures.In this proposal also exemplified how to use PGP as a reliable security systems, engineeringand implementation of PGP encryption in PGP in the digital signature. PGP is also used tosecure e-mail sent or received by users. [1]